Diffuse large B-cell lymphoma of the small intestine in a patient with refractory coeliac disease. - Ahmad Affandi, Khairunisa; Abd Shukor, Nordashima; Mohamed Rose, Isa; Raja Ali, Raja Affendi; Masir, Noraidah (College of Pathologists, Academy of Medicine Malaysia, 2019)
INTRODUCTION: Coeliac disease enteropathy is associated with an increased risk of lymphomas. Enteropathy-associated T-cell lymphoma is the principal malignancy related to coeliac disease. However, studies have shown that other types of lymphoma such as diffuse large B-cell lymphoma may also be associated with coeliac disease.